(untitled) (Journal of the Bangladesh Agricultural University, 2014)
An experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during June to December 2012 with a view to finding out the effect of variety and nitrogen fertilizer application on the growth and yield of transplant Aman rice. The experiment comprised four varieties viz. BRRI dhan33, BRRI dhan34, BRRI dhan39 and BRRI dhan46, and four levels of nitrogen viz. control (no urea), prilled urea (50 kg N ha-1), one pellet (0.9g) of USG/4 hills of two adjacent rows (30 kg N ha-1) was applied at 10 DAT and two pellets of USG (0.9g each) one applied at 10 DAT and the other at 45 DAT/4 hills of two adjacent rows (60 kg N ha-1). The experiment was laid out in a randomized complete block design with three replications. Results of the experiment showed that variety and level of nitrogen application had significant effect on yield attributes and yield of transplant Aman rice. At maturity the tallest plant (122.60 cm) and the highest number total tillers hill-1 (12.72) were observed in two pellets of USG/4 hills providing 60 kg N ha-1. The highest number of tillers hill-1 (10.08) was obtained from BRRI dhan34 and the lowest one (9.88) from BRRI dhan33. The highest grain yield was obtained from BRRI dhan46 (4.56 t ha-1) and the lowest one (3.27 t ha-1) was obtained from BRRI dhan34. The interaction reveals that the highest grain yield (5.61 t ha-1) was obtained from the treatment combination of BRRI dhan46 with two pellets of USG (0.9g each) applied one at 10 DAT and the other at 45 DAT. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21239 J. Bangladesh Agril. Univ. 12(1): 55-60, June 2014